2005
DOI: 10.1111/j.1468-0297.2005.01041.x
|View full text |Cite
|
Sign up to set email alerts
|

Can Private Learn from Public Governance?

Abstract: Corporate governance is importantly based on agency theory and relies on extrinsic incentives to align the interests of managers, employees and shareholders. This article argues that in view of recent corporate scandals, private governance can learn from public governance: (1) Goaloriented intrinsic motivation of agents should be supported by fixed incomes and an extensive selection process of employees; (2) Extrinsic, but non-monetary incentives (e.g. conferring orders and titles) can be used; (3) The power o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…Although recognition-based incentives might have quite different motivational mechanisms than monetary compensation, research suggests they may produce comparable, or in some cases superior, results. Recognition may bolster an agent's intrinsic motivation or engender less negative reactions among coworkers than pecuniary awards (Frey & Benz, 2005). In Heinrich's (2007) study of performance bonus awards in the Workforce Investment Act (WIA), she observed that performance bonuses paid to states tended to be low powered, in terms of both the proportion of performance-contingent funds to total program funding and the lack of relationship between WIA program employees' performance and how bonus funds were expended by the states.…”
Section: Employee Motivations and Choice Of Actionmentioning
confidence: 99%
“…Although recognition-based incentives might have quite different motivational mechanisms than monetary compensation, research suggests they may produce comparable, or in some cases superior, results. Recognition may bolster an agent's intrinsic motivation or engender less negative reactions among coworkers than pecuniary awards (Frey & Benz, 2005). In Heinrich's (2007) study of performance bonus awards in the Workforce Investment Act (WIA), she observed that performance bonuses paid to states tended to be low powered, in terms of both the proportion of performance-contingent funds to total program funding and the lack of relationship between WIA program employees' performance and how bonus funds were expended by the states.…”
Section: Employee Motivations and Choice Of Actionmentioning
confidence: 99%
“…For example, the intrinsic motivation can be crowded out by extrinsic rewards and punishments in a public-sector organisation, for example if employees become alienated by managerialism and sticks and carrots (as inspired by the New Public Management). It has even been argued that the private sector should learn from traditional public-sector organisations to rely on intrinsic motivation, to implement career paths that discourage opportunism, and to apply nonpecuniary rewards (Frey and Benz, 2005).…”
Section: Why Would Ownership Matter?mentioning
confidence: 99%
“…Frey and Benz () and Benz and Frey () go beyond the pure resemblance and suggest that due to the existing similarities, corporate governance might learn from the rich literature on public governance. Agency theory is an important theoretical approach in both corporate and public sector economics and there are many institutional similarities.…”
Section: Auditors In the Public Sectormentioning
confidence: 99%
“…Thus, controlling the agents requires overcoming the free-rider problem, acquiring information, and orchestrating possible countermeasures, such as coordinated voting against decisions taken by the agents, etc. Frey and Benz (2005) and Benz and Frey (2007) go beyond the pure resemblance and suggest that due to the existing similarities, corporate governance might learn from the rich literature on public governance. Agency theory is an important theoretical approach in both corporate and public sector economics and there are many institutional similarities.…”
Section: Analogies Between the Corporate And The Public Sectormentioning
confidence: 99%
See 1 more Smart Citation